Exposure of wildlife to anthrax in Kruger and Etosha National Parks and the effect of haemoparasite coinfections - Van Heerden, Henriette (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science Tropical Diseases))--University of Pretoria, 2020.